Utveckling av modulärt tvärbalksprogram - Sjödin, Stina (2011)
Scania's modular production system makes a lot of adjustments possible, while costs for product development, production and spare parts are kept low. One of Scania's modular systems was the one for welded crossmembers. Scania uses a casted crossmember in their trailer truck for 4x2 chassis with air suspension. Because of the relatively high production costs for the casted crossmember a welded crossmember has been designed earlier on Scania. The design of the welded crossmember was not complete because it missed solutions for attachment of valves. This project was in collaboration between Scania in Södertälje and Ferruform in Luleå. The design of the crossmember was carried out in Södertälje and the production part of the project was carried out in Luleå. The goal of the project was to design a modular crossmember program for welded crossmembers and to suggest production line for the beams. Crossmembers with similar production operations were analyzed to minimize production costs. The welded air suspension beam should be fully designed. The beams studied were all closed, welded crossmembers which required production operations of pressing, welding and machining. The beams studied were air suspension beam of 4x2 chassis frame, GB-tipperbeam and two different endbeams. None of the beams could directly be combined because the stiffness differed too much, however the beams could be redesigned to facilitate the production. Three new air suspension beams and two new GB-tipper beams was designed and the strength of the welds were studied using Finite element analysis for the current load cases. The results showed that the stresses in both air suspension beam and GB-tipperbalken decreased with the new design. A proposal for a production line for welded crossmembers was developed with production operations, cutting, pressing, welding, machining, finishing and assembly. To manage the entire flow of crossmembers three NCmachines were needed and one laser machines. Calculations showed that the air suspension beam would lower ...